"THE APPROACH TO TEACHING ENGLISH TO STUDENTS OF ECONOMICS” - Usmonov Sunatillo Buriboyevich (Ustozlar uchun, 2025)
The last several years have seen a growing interest in teaching English for Specific Purposes (ESP) in Uzbekistan. There is a vast array of textbooks and reading materials for ESP courses, yet most of them deal with business and medicine, law, economy etc., while there is still a shortage of ready to use materials concerning such fields as, for example, economy. The present paper presents the design process of an English for Specific Purposes (ESP) course addressed to students of economy at the Faculty of Management and economics in Samarkand State University.